Retorik dalam novel-novel Abdullah Hussain - Baharum, Sobariah (2008)
Rhetoric means the art, competence and effective usage of language, either in oral or writing. In communication, rhetoric is the skill and competence of speaking, using the language effectively in order to win over an audience or a listener. In essay writing, rhetoric is the art of using attractive writing style; beautiful and effective word choices with the goal of influencing the reader. The understanding of this concept guides the researcher to make a study in linguistic field with five Abdullah Hussain’s novels being used as the subject of the study. The rational for these novels as the subject of the study is the genre relevance as rhetoric tool because novels are not read just for fun or amusement but they serve as a medium for disseminating the author’s ideas, ideologies or discourses about human life or events to the reader too. Even though many studies on Malay novels had been carried out by local scholars, an exhaustive linguistic study that focuses on the rhetoric elements is quite rare. Base on the researcher searches on the Malay corpus, most of these linguistic studies are based on the rhetoric elements usage in advertisement, public speaking, and poems. This descriptive study is based on the Rhetoric Theory. The content analysis approach is used to examine the texts’ context and contextual elements. The main objective or focus of the study is to identify the type, structure, form, and the style of the rhetoric used in these Abdullah Hussain’s novels. Besides that, this research is to examine and explain the relations between the rhetoric signs in the texts vis a vis to their functions and to the author’s ideas. The findings of this research shows that the author used five types of rhetoric in his novels, namely, narrative, descriptive, exposition, argumentative and persuasive. From the structural analysis perspective, the rhetoric types used in the novels are the grammatical and lexical items, phrases, clauses, sentences as well as discourses. The research findings reveal that the author’s rhetoric style usage includes comparative stylistic, repetition and highlighting, confrontational approaches and extensive usage of linguistic forms of proverb and metaphor. And, the analysis of the rhetorical signage reveals that these rhetoric signs have direct relation to the author ideas of propagating his social critiques to his readers. Hence, rhetoric is an important element utilized in the writing of an author to gloss up his works as well as to win over his audience.